Efficacy of oral versus long-acting antipsychotic treatment in patients with early-phase schizophrenia in Europe and Israel: a large-scale, open-label, randomised trial (EULAST). (March 2023) - Winter-van Rossum, Inge; Weiser, Mark; Galderisi, Silvana; Leucht, Stefan; Bitter, Istvan; Glenthøj, Birte; Hasan, Alkomiet; Luykx, Jurjen; Kupchik, Marina; Psota, Georg; Rocca, Paola; Stefanis, Nikos; et al.
Summary: Background: Schizophrenia is a severe psychiatric disorder with periods of remission and relapse. As discontinuation of antipsychotic medication is the most important reason for relapse, long-term maintenance treatment is key. Whether intramuscular long-acting (depot) antipsychotics are more efficacious than oral medication in preventing medication discontinuation is still unresolved. We aimed to compare time to all-cause discontinuation in patients randomly allocated to long-acting injectable (LAI) versus oral medication. Methods: EULAST was a pragmatic, randomised, open-label trial conducted at 50 general hospitals and psychiatric specialty clinics in 15 European countries and Israel. Patients aged 18 years and older, with DSM-IV schizophrenia (as confirmed by the Mini International Neuropsychiatric Interview 5 plus) and having experienced their first psychotic episode from 6 months to 7 years before screening, were randomly allocated (1:1:1:1) using block randomisation to LAI paliperidone, LAI aripiprazole, or the respective oral formulations of these antipsychotics. Randomisation was stratified by country and duration of illness (6 months up to 3 years vs 4 to 7 years). Patients were followed up for up to 19 months. The primary endpoint was discontinuation, regardless of the reason, during 19 months of treatment. We used survival analysis to assess the time until all-cause discontinuation in the intention-to-treat (ITT) group, and per protocol analyses were also done. This trial is registered with ClinicalTrials.gov, NCT02146547, and is complete. Findings: Between Feb 24, 2015, and Dec 15, 2018, 533 individuals were recruited and assessed for eligibility. The ITT population included 511 participants, with 171 (33%) women and 340 (67%) men, and a mean age of 30·5 (SD 9·6) years. 410 (80%) of 511 participants were White, 35 (7%) were Black, 20 (4%) were Asian, and 46 (9%) were other ethnicity. In the combined oral antipsychotics treatment group of 247 patients, 72 (29%) patients completed the study and 175 (71%) met all-cause discontinuation criteria. In the combined LAI treatment arm of 264 patients, 95 (36%) completed the study and 169 (64%) met the all-cause discontinuation criteria. Cox regression analyses showed that treatment discontinuation for any cause did not differ between the two combined treatment groups (hazard ration [HR] 1·16, 95% CI 0·94–1·43, p=0·18). No significant difference was found in the time to all-cause discontinuation between the combined oral and combined LAI treatment groups (log rank test χ 2 =1·87 [df 1]; p=0·17). During the study, 121 psychiatric hospitalisations occurred in 103 patients, and one patient from each of the LAI groups died; the death of the patient assigned to paliperidone was assessed to be unrelated to the medication, but the cause of other patient's death was not shared with the study team. 86 (25%) of 350 participants with available data met akathisia criteria and 70 (20%) met parkinsonism criteria at some point during the study. Interpretation: We found no substantial advantage for LAI antipsychotic treatment over oral treatment regarding time to discontinuation in patients with early-phase schizophrenia, indicating that there is no reason to prescribe LAIs instead of oral antipsychotics if the goal is to prevent discontinuation of antipsychotic medication in daily clinical practice. Funding: Lundbeck and Otsuka.